Det kgl. Landhusholdningsselskabs Generalforsamling den 18de December 1878. - la Cour, J. C. (Tidsskrift for Landøkonomi, 2018)
Det kgl. Landhusholdningsselskabs Generalforsamling den 18de December 1878.